Numerical investigation on solidification in casting using ProCAST - Dubey, Shashank; Swain, Smruti Rekha (IOP conference series. Materials Science and Engineering, 2019)
This work deals with elimination of defects in aluminium alloy castings produced by gravity sand casting process. The main intention of the work is to investigate the defectsand improve quality of a gravity sand cast component using Computer Aided CastingSimulation Software. In this study aluminium alloy gravity sand casting solidification hasbeen selected as a subject of study. The mould filling process and solidification weresimulated for detection of casting defects and hence optimization of the casting process. Themajor defects in the components are identified to be solidification shrinkage porosity defects.ProCAST simulation software is used for simulating the solidification process of casting andvisualizing outputs showing possible problematic areas or defects which may occur in the castproduct.